2014
DOI: 10.1186/1754-6834-7-101
|View full text |Cite
|
Sign up to set email alerts
|

Zymomonas mobilis: a novel platform for future biorefineries

Abstract: Biosynthesis of liquid fuels and biomass-based building block chemicals from microorganisms have been regarded as a competitive alternative route to traditional. Zymomonas mobilis possesses a number of desirable characteristics for its special Entner-Doudoroff pathway, which makes it an ideal platform for both metabolic engineering and commercial-scale production of desirable bio-products as the same as Escherichia coli and Saccharomyces cerevisiae based on consideration of future biomass biorefinery. Z. mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
145
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 168 publications
(168 reference statements)
0
145
0
2
Order By: Relevance
“…Vanillin, syringaldehyde and 4-HB are formed by the degradation of lignin. The presence of these compounds has been shown to synergistically reduce the growth rate of microorganisms by disturbing the cell membrane function, inhibiting essential enzymes, negatively interacting with DNA and RNA, and specifically interacting with the Entner Doudoroff pathway mRNA (Banerjee et al, 1981;Franden et al, 2013;He et al, 2014). Despite these adverse conditions, we found that rice straw hydrolysate can be used by Z. mobilis (strains TISTR405, 550 and 551) in biofilms on polystyrene surfaces (3 days old) to produce higher ethanol yields (Y P/S ) than planktonic or suspended cultures (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Vanillin, syringaldehyde and 4-HB are formed by the degradation of lignin. The presence of these compounds has been shown to synergistically reduce the growth rate of microorganisms by disturbing the cell membrane function, inhibiting essential enzymes, negatively interacting with DNA and RNA, and specifically interacting with the Entner Doudoroff pathway mRNA (Banerjee et al, 1981;Franden et al, 2013;He et al, 2014). Despite these adverse conditions, we found that rice straw hydrolysate can be used by Z. mobilis (strains TISTR405, 550 and 551) in biofilms on polystyrene surfaces (3 days old) to produce higher ethanol yields (Y P/S ) than planktonic or suspended cultures (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This is considered as a promising strategy for reducing the production costs (Lynd et al 2005;Cardona and Sanchez 2007;Xu et al 2009;He et al 2014). CBP microbes for ethanol production from lignocellulosic materials can be developed using native cellulolytic microbes that are engineered to improve ethanol production, e.g., Trichoderma reesei, Aspergillus, and Fusarium (Ruiz et al 2007;Xu et al 2009, Piriya et al 2012, or engineered noncellulolytic organisms that exhibit high native ethanol production, e.g., Z. mobilis and Saccharomyces cerevisiae (Van Zyl et al 2007;Linger et al 2010;Apiwatanapiwat et al 2011;Vasan et al 2011;Den et al 2015;Gonçalves et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to the other Gramnegative bacteria, the presence of an outer membrane results in an inefficient protein secretion, which is a major technical challenge in engineering cellulolytic Z. mobilis (Jung et al, 2012). Recently, Jung et al (2012) and He et al (2014) reviewed the studies focused on expression of cellulase enzymes in this bacterium. Endoglucanase genes such as B. subtilis endo-β-1,4-glucanase gene (Yoon et al, 1988), Enterobacter cloacae endoglucanase gene (Thirumalai et al, 2011), eglX (Lejeune 1988), CMCase (Misawa et al, 1988;Okamoto et al, 1994), and celZ (Brestic-Goachet et al, 1989) were reportedly expressed in Z. mobilis.…”
Section: Zymomonas Mobilismentioning
confidence: 99%